Profile injuries and musculoskeletal abnormalities of elite wushu athletes - Mohammad Reza Changizi; Nader Rahnama (Turkish Journal of Kinesiology, 2017)
The objective of this study was to investigate the profile of sports injuries and postural abnormalities of elite wushu athletes. Participants were recruited purposefully (n = 51, age 16.3 (4.9 years, height 165.4 (13.9 cm and weight 52.6 (14.7 kg) and informed consent participated in the study. Injury report form (including type, anatomic site, etiology and mechanism of injury) was used to record the damage. Posture was assesses using Grid Chart, flexible ruler, calipers and mirror box were performed. In order to analyze the data, descriptive and inferential statistical methods, chi-square was used. 166 injuries and 167 postural abnormalities were recorded. Injury type, anatomical location, and mechanism of injury and abnormalities in elite status was significantly different (P>0.05). 6.85 injuries per 1000 hours exposure and the risk of 8.91 injuries per 1000 athlete exposures was estimated. The most common types of injury were contusion (36.7%), hematoma (20.5%) and abrasions (13.3%) respectively. Based on the anatomic site of injury, lower extremities (47.6%), head and face (25.9%), upper extremities (13.9%) and trunk (12.7%) were injured mostly respectively. Opponent's Blow down technique (24.7%), previous injury (16.3%), lack of physical fitness (12.7%) and fatigue (12%) were in top priority. Receiving kicks (21%), Receiving punches (13.8%) and throwing technique by opponent (12%) were the most common mechanisms of injury. Flat foot (29.3%), uneven shoulders (25.7%) and scoliosis (16.2%) were the most common postural abnormalities.